A Structural Equation Modeling (SEM) Approach to Examine The Impact of Gold Futures Price Spillovers, Dividend Announcements, and Investor Attention on Abnormal Returns among 32 Indonesian Listed Companies Distributing Dividends in 2024 - Surahman, Arif; Rusnaeni, Nani (International Journal of Science, Technology & Management, 2026)
The purpose of this study is to examine the effects of investor interest, dividend announcements, and spillovers in the price of gold futures on abnormal returns among 32 Indonesian listed businesses that paid dividends in 2024. The study examines the direct and indirect correlations between the variables using a quantitative approach and the Structural Equation Modeling (SEM) technique with Partial Least Squares (PLS) estimate in SmartPLS 3.0. The Indonesia Stock Exchange (IDX), corporate financial reports, and worldwide gold market statistics were the sources of secondary data. Trading volume was used as a stand-in for investor attention, and abnormal returns were measured using an event-study framework with a two-day window surrounding the cum-dividend date. The findings indicate that neither dividend announcements nor spillovers in the price of gold have a statistically significant impact on abnormal returns. While there is a weak positive correlation between dividend announcements and gold prices, there is a negative correlation, indicating a safe-haven substitution effect where investors move away from stocks as gold prices rise. Furthermore, investor attention does not mediate the relationship between the independent variables and the dependent variable, nor does it significantly affect abnormal returns. While investor attention shows very low predictability (R² = 0.002), the model shows a moderate explanatory power for abnormal returns (R² = 0.434) and a high predictive relevance (Q² = 0.435). Overall, the results show that the Indonesian capital market reacts to corporate and macroeconomic information primarily through direct effects rather than behavioral mediation. By emphasizing the restricted function of investor attention as an information-transmission channel, this study adds to the body of knowledge on behavioral finance and spillover dynamics in emerging countries. To improve the explanatory power of abnormal return models, it is advised that future research incorporate more comprehensive behavioral or sentiment factors.